Occurrence and Effect of Hypomagnesemia in Patients Suffering from Guillain-Barre Syndrome in Intensive Care Unit - Rahman, AKM Ferdous; Reza, Syed Tariq; Asaduzzaman, Muhammad; Satter, Kamrun; Akter, Salma; Salim, Md; Rahman, M Abdur (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Background: Predicting patient outcome is an important component of patient care in the critical care units. It has a vital importance to the intensivists. Because it allows the planning of early aggressive therapeutic interventions, optimum resource allocation and appropriate counseling of the family as well as the patient. So the intensivists have developed a number of prognostication tools for the patient admitted to ICU for above purpose. The two widely adopted systems to predict mortality are the Acute Physiology Assessment Chronic Health Evaluation (APACHE2) & Simplified Acute Physiology Score(SAP).Though useful, these tools are complex & require input of a large number of variables derived from patients history, physical examination & initial laboratory data. In several studies, it has been shown that serum magnesium level has great effect on mortality & morbidity in critically ill patient. But there is no study to observe the effect of hypomagnesium on the outcome of GBS in ICU. Methods and materials: A prospective observational study in the intensive care unit of DMCH from January 2014 to December 2015. Thirty patients admitted to the ICU with suspected GBS requiring intensive care for more than at least 2 days with age more than 18 years were included. A blood sample was collected for estimation of serum total magnesium level on the day of admission to ICU. Finally all collected data were tabulated and analysed using standard statistical methods by SPSS version 17 for Windows. The Chisquare test was applied to correlate hypomagnesemia & normomagnesemia with the outcome. Result: Total numbers of patients were thirty. 40% of patient had been suffering from hypomagnesemia. 40% patient needed mechanical ventilation.The mean length of mechanical ventilation days were higher in hypomagnesemic patients than normomagnesemic with were 17.66±8.40 vs 12.05±3.68 days. The mean length of ICU stay were 20.50(±9.48) days in hypomagnesemia and 14.22(±3.33) days in normomagnesemics. 33.33% patient had hyponatremia,58.33% patient had hypokalemia,50% patient had hypocalcemia. 50% patients with hypomagnesemia had sepsis. :Mortality rate in hypomagnesemic patients were 80% that were 20% in normomagnesemia. Conclusion: Hypomagnesemia has played a pivotal role in prediction of mortality and morbidity in GBS. So hypomagnesemia can be used as a prediction tool for patient suffering from GBS in ICU. JBSA 2017; 30(1): 21-26